The Role of Fatigue in Return to Sport Testing Following Anterior Cruciate Ligament Reconstruction - Justin C Tallard; Corbin Hedt; Bradley S Lambert; Patrick C McCulloch (International Journal of Sports Physical Therapy)
# Background Fatigue may play a role in anterior cruciate ligament (ACL) injury, but has not been incorporated into objective test batteries for return to sport decisions following ACL reconstruction (ACLR) surgery. The effect of fatigue on muscle function and performance following surgery and rehabilitation has been poorly studied.